Chemical composition of Pacific and Indian Ocean manganese nodules and crusts from the DOMES area and the NIXO-CNEXO campaign using X-ray emission spectrometry - Mary B Fisk; Jane Z Frazer; R W Fitzgerald (PANGAEA, 2023)
Manganese nodules and crusts from the Pacific Ocean were analyzed at Scripps Institution of Oceanography using X-ray emission spectrometry (XES). Samples were ground to < 74 microns, pressed into pellets and dried at 110 Degrees Centigrade. They were analyzed by XES for 400 seconds.